MAKNA SIMBOLIK DAN PESAN SELF HEALING DALAM LIRIK LAGU SECUKUPNYA KARYA HINDIA: ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE - Ryan Subastian; Nunik Hariyani; Fikri Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the symbolic meaning and self-healing messages in the lyrics of Secukupnya by Hindia using Ferdinand de Saussure's dyadic semiotics (signifier, signified, sign). Released on May 3, 2019 as the second single from the album Menari dengan Bayangan (2019), the song addresses existential anxiety about the future, economic precarity, collective failure, family wounds, nostalgic escape, and decay, before arriving at a resolution centered on measured grief and cyclical impermanence. This descriptive qualitative study employs a content analysis method. Data were collected through documentation and literature review, then analyzed systematically using Saussurean semiotic tables. Self-compassion theory (Neff, 2003, 2011) serves as a supporting conceptual framework. Results identify four dominant sign clusters: (1) anxiety and structural pressure signs; (2) collective failure and solidarity signs; (3) wounds, decay, and nostalgic escape signs; and (4) measured grief and cyclical impermanence signs. Contrary to its surface meaning as 'sufficient rest,' the word 'secukupnya' undergoes a significant semiotic shift across the song from a threshold that has been exceeded (negative) to a healthy unit of grieving (positive). The common humanity component of self-compassion emerges as the most dominant and explicit dimension, particularly through the sign 'we all fail' and the inverted toast ritual of grieving together, while mindfulness and self-kindness appear more implicitly. This study contributes to popular music semiotics in Indonesia and demonstrates that the song offers a socially relational, rather than purely individual, model of self-healing.